The Effect of Problem Based Learning Assisted By Padlet on Students Collaboration and Critical Thinking Skills - Syintia; Mahesi Agni Zaus; Vera Irma Delianti; Rizkayeni Marta (Universitas Negeri Padang, 2025)
This research is motivated by the finding that indicate a low collaboration and critical thinking skills of students, allegedly caused by students tendency to be passive and only receive instructions during learning, the learning models used such as simple discussions with LKPD and presentation media that are less supportive do not provide optimal learning experiences. This research was conducted in Class X TJKT using a quasi-experimental design. Data were collected through observation sheets and tests. The analysis of the research data employed an independent sample t-test. The results of the collaboration ability assessment revealed a thiut value of 19.507 with a significance level (Sig. 2-tailed) of 0.000, indicating that the tcount value was greater than the ttable value of 1.667. Similarly, the analysis of students critical thinking ability yielded a tcount value of 6.025 with a significance level (Sig. 2-tailed) of 0.000, confirming that the tcount value exceeded the ttable value of 1.667. Therefore, it can be concluded that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. The Problem-Based Learning model, assisted by Padlet, has a significant effect on students collaboration and critical thinking skills.